Biology, Volume 1 - Robinson, Richard (Macmillan Reference USA, 2012)
In response to the popularity and critical acclaim of its other full-color science sets for students, Macmillan Reference USA has developed a comprehensive series of colorful, informative sets in the sciences. The Macmillan Science Library for Students will engage students at many levels -- from middle school and high school -- to nonmajors in college and lay readers in public libraries. This new series offers the most comprehensive views of key areas in the world of science. Each set explores all facets of the topic, offering not only descriptive and analytical information, but also cultural and ethical issues, and career opportunities in many fields of science.